PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2010-2016) - Nur’ Adilla (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the effect of liquidity, solvency, profitability, and growth of manufacturing companies. The independent variables are liquidity (current ratio), solvency (debt to equity ratio), profitability (return on assets), and growth of companies (growth of assets). The dependent variable of this study is dividend policy that measured using dividend payout ratio. This research is a generalization quantitative research, which uses the sample as a representation of research population. The population in this study amounted to 121 manufacturing companies. Sampling use nonprobability sampling method and the technique of determining the sample using purposive sampling. This study uses secondary data obtained from annual financial reports of manufacturing companies from the Indonesia Stock Exchange period 2010-2017. Data analysis used in this research is Multiple Regression analysis. This study uses a partial test that shows the result that liquidity and profitability have a significant influence on the positive direction of dividend policy. While solvability and corporate growth have a significant negative effect on the dividend policy. Keywords: liquidity (current ratio), solvency (debt to equity ratio), profitability (return on assets), growth of companies (growth of assets), and dividend policy (dividend payout ratio).